Experimental and Numerical Dynamic Investigation of an ORC System for Waste Heat Recovery Applications in Transportation Sector - Matteo Marchionni; Fabio Fatigati; Marco Di Bartolomeo; Davide Di Battista; Mario Petrollese (Energies, 2022)
ORC power units represent a promising technology for the recovery of waste heat in Internal Combustion Engines (ICEs), allowing to reduce emissions while keeping ICE performance close to expectations. However, the intrinsic transient nature of exhaust gases represents a challenge since it leads ORCs to often work in off-design conditions. It then becomes relevant to study their transient response to optimize performance and prevent main components from operating at inadequate conditions. To assess this aspect, an experimental dynamic analysis was carried out on an ORC-based power unit bottomed to a 3 L Diesel ICE. The adoption of a scroll expander and the control of the pump revolution speed allow a wide operability of the ORC. Indeed, the refrigerant mass flow rate can be adapted according to the exhaust gas thermal power availability in order to increase thermal power recovery from exhaust gases. The experimental data confirmed that when the expander speed is not regulated, it is possible to control the cycle maximum pressure by acting on the refrigerant flow rate. The experimental data have also been used to validate a model developed to extend the analysis beyond the experimental operating limits. It was seen that a 30% mass flow rate increase allowed to raise the plant power from 750 W to 830 W.